"Tenemos que ser la voz": Exploring resilience among Latina/o immigrant families in the context of restrictive immigration policies and practices. (November 2020) - Arce, M. Alejandra; Kumar, Jessica L.; Kuperminc, Gabriel P.; Roche, Kathleen M.
Highlights: Latina/o immigrant parents of all residency statuses (i.e., undocumented, TPS holders, permanent residents, and U.S. citizens) rely on both internal (i.e., faith) and external (i.e., social support) sources of resilience to protect themselves and their families against the negative effects of restrictive immigration policies and practices. Civic commitment and action (an internal and external source of resilience) was discussed more frequently as being emphasized and/or enacted by those with greater protections in terms of their residency status. Latina/o immigrant parents of all residency statuses described being aware that the TPS and DACA programs were under threat at the time of this investigation and expressed their support for keeping these programs in place. TPS holders may have been less optimistic about the future of these programs. Abstract: Research investigating associations between immigration policies and practices and indicators of mental health among Latina/o immigrant families has identified a number of risk factors for this population, such as family separation. The role of protective factors tied to the mental health of Latina/o immigrants, however, often has been neglected. This study explored internal and external sources of resilience that may protect Latina/o immigrant families against the potentially negative effects of restrictive immigration policies and practices on psychological well-being. Six focus groups (N = 50) were conducted with Latina/o immigrant parents of varying residency statuses (i.e., undocumented, permanent residents, Temporary Protected Status (TPS) holders, and U.S. citizens). Data were analyzed using thematic analysis. Three themes were identified: Social Support, Faith, and Civic Commitment and Action. Across groups, Latina/o parents referenced family, peer, and community support, as well as their spiritual faith and involvement in advocacy efforts as coping mechanisms. Overall, results suggest that Latina/o immigrant parents of varying residency statuses rely on both internal and external sources of resilience to protect themselves and their families when navigating restrictive immigration policies and practices. This research is particularly timely in light of the increasingly restrictive nature of immigration policies in the U.S. and the growing literature on the influence these may have on immigrant well-being. Intervention efforts should build upon existing strengths, such as providing opportunities for Latina/o immigrant families to participate in political activism.